Changes in peripheral lymphocyte populations in patients with advanced/recurrent ovarian cancer undergoing splenectomy during cytoreductive surgery - Wei Chen; Shuang Ye; Yutuan Wu; Xuan Pei; Libing Xiang; Bo Ping; Boer Shan; Huijuan Yang (BMC, 2021)
Abstract Background To investigate changes in peripheral lymphocyte subsets after splenectomy during cytoreductive surgery for advanced or recurrent ovarian cancers. Methods We enrolled 83 patients with advanced or recurrent ovarian cancer who underwent cytoreductive surgery. Twenty patients who also underwent splenectomy were assigned to the splenectomy cohort and the rest were assigned to the non-splenectomy cohort. Flow cytometry was used to measure peripheral lymphocyte subsets consisting of T cells, regulatory T cells, natural killer cells, B cells, and activation antigens before and after surgery. Results There was no difference in the number and distribution of peripheral lymphocyte subsets between the two cohorts before surgery. After surgery, we observed elevated levels of T cells (CD3+, CD3+CD8+) in the splenectomy cohort compared to those in the non-splenectomy cohort, and the difference was statistically significant. CD8+CD28+ T cells had a significant decreasing tendency (P = 0.011) while CD3+/HLA-DR+ T cells showed the opposite trend (P = 0.001) in the splenectomy cohort. The proportion of Tregs (P = 0.005) and B cells (P < 0.001) including CD3−/HLA-DR+ B cells (P = 0.007) increased after surgery, and the absolute number of T cells and NK cells decreased to different extents (P < 0.001) in the non-splenectomy cohort. The post-operative percentage of CD8+CD28+ T cells was less than the pre-operative percentage (P = 0.022), which was similar to the splenectomy cohort. There was no significant difference in progression-free survival or overall survival between the groups after a median follow-up time of 41 months. Conclusions The changes in peripheral lymphocyte populations were different between patients with and those without splenectomy during cytoreductive surgery for ovarian cancers. T cells were increased and activated in the splenectomy cohort, whereas, B cells were increased and activated in the non-splenectomy cohort.